Working Principles of Lithium Metal Anode in Pouch Cells - Liu, He; Sun, Xin; Cheng, Xin‐Bing; Guo, Cong; Yu, Feng; Bao, Weizhai; Wang, Tao; Li, Jingfa; Zhang, Qiang (Advanced energy materials, 2022)
Lithium metal battery has been considered as one of the potential candidates for next‐generation energy storage systems. However, the dendrite growth issue in Li anodes results in low practical energy density, short lifespan, and poor safety performance. The strategies in suppressing Li dendrite growth are mostly conducted in materials‐level coin cells, while their validity in device‐level pouch cells is still under debate. It is imperative to address dendrite issues in pouch cells to realize the practical application of Li metal batteries. This review presents a comprehensive overview of the failure mechanism and regulation strategies of Li metal anodes in practical pouch cells. First, the gaps between the scientific findings in materials‐level coin cells and device‐level pouch cells are underscored. Specific attention is paid to the mechanistic understanding and quantitative discussion on the failure mechanisms of pouch‐type Li metal batteries. Subsequently, recently proposed strategies are reviewed to suppress dendrite growth in pouch cells. The state‐of‐the‐art electrochemical performance of pouch cells, especially the cell‐level energy density and lifespan, is critically concerned. The review concludes with an attempt to summarize the scientific and engineering understandings of pouch‐type Li metal anodes and propose some novel insights for the practical applications of Li metal batteries. This review presents a comprehensive overview of the gaps between the materials‐level coin cells and device‐level pouch cells, mechanistic understanding and quantitative discussion for failure mechanisms of pouch‐type Li metal anodes, and the recently proposed strategies to suppress dendrite growth in pouch cells.